Silver nanocomposites: Polyvalent composite materials (REVISTA SAYWA, 2021)
Silver nanoparticles (AgNPs) have been becoming a promising alternative for obtaining new antibacterial agents. However, numerous investigations have been found that have identified that the AgNPs present toxicity to eukaryotic cells, generating inflammatory, oxidative and genotoxic consequences due to their low specificity for a white tissue (tissue to which the treatment is directed), as well as the contamination in the water where they have been used (water contamination), generating concern at the environmental level. One of the alternatives for this type of problem is the use of a magnetic nucleus in the silver nanoparticles that would improve the separation and reuse processes, through the formation of silver nanocomposites (AgNCs). In this way the AgNCs could be used as a bactericidal agent which after being used could be removed, thus avoiding contamination of the medium in which it is applied.